Between and within-year effects of haying on grassland bird - Faria, Nuno (2017)
In recent years, haying has extended to Iberian Mediterranean dry grasslands potentially threatening grassland birds. We evaluate the between and within-year effects of haying on grassland birds in Alentejo region, Portugal. Our main goals were: (1) to investigate variations on bird abundance and species richness in the fields hayed, with respect to past haying events occurred in a field and its surroundings and (2) to investigate the shifts in bird abundance, species richness and spatial dynamics resulting from haying a field and its surrounding area in a given year. We conducted grassland bird censuses during the breeding season through point counts from 2012 to 2015. The relationship between bird abundance/richness and past haying events was investigated using Generalized Linear Models whereas within-year effects of haying were analysed using Generalized Additive Models. Bird abundance in a field was positively related with the surface hayed in the vicinity of that field in the previous year. However, contrasting yearly effects were found for non passerines. Also, some species prefer fields with less haying events or surface hayed, whereas others occur mostly in fields frequently managed for haying. Haying a field leads, in the short term, to its abandonment by birds, and thus to a decrease in bird abundance and, for some species, to spatial concentration in surrounding fields offering suitable habitat. We conclude that within-year effects of haying have higher impact on grassland birds than between-year effects. Maintaining haying at low levels by rotating haying yearly through the different fields in each farm and using partial haying may be an adequate way to ensure an effective management of grassland bird populations.